Let:
![\begin{gathered} y=-x^2+8x+18_{\text{ }}(1) \\ y=-2x^2-16x-30_{}(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/62m2mc7rbuv64hlxiokgdned5ybgplzgx8.png)
Using elimination:
![\begin{gathered} (1)-(2) \\ y-y=-x^2-(-2x^2)+8x-(-16x)+18-(-30) \\ 0=x^2+24x+48 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/accjh96rnx1dy66gh4hikrzn3to60ptyet.png)
Subtract 48 from both sides:
![\begin{gathered} x^2+24x=-48 \\ \text{add 144 to both sides} \\ x^2+24x+144=96 \\ \text{Factor:} \\ (x+12)^2=96 \\ x=4\sqrt[]{6}-12\approx-2.202 \\ or \\ x=-12-4\sqrt[]{6}\approx-21.798 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pdme6cyssi97q1wxwa43gnhg6dk6zhve9n.png)
Let's check the solutions:
![\begin{gathered} y=-(-2.202)^2+8(-2.202)+18=-4.465 \\ y=-2(-2.202)^2-16(-2.202)-30=-4.465 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kh6j8vdt1f0u2bazls3xxt25ybu1nccy5u.png)
The first solution satisfies the system, therefore, it is a valid solution
![\begin{gathered} y=-(-21.798)^2+8(-21.798)+18=-282.7688 \\ y=-2(-21.798)^2-16(-21.798)-30=-631.53 \\ -282.7688\\e-631.53 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tqac3k92ye62d0in2tg7ohqbxstefmwxgv.png)
This solution doesn't satisfy the system, therefore, it is not a valid solution.
Hence, the system have only one solution and it is:
![(2.202,-4.465)](https://img.qammunity.org/2023/formulas/mathematics/college/r6q66o08l9qn5f0ckpuslx12knusbe3eq8.png)